2017
DOI: 10.1053/j.tcam.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nandrolone Decanoate in Treatment of Pure Red Cell Aplasia Secondary to Diclofenac Administration: A Case Report

Abstract: Pure red cell aplasia (PRCA) is a disorder that leads to a nonregenerative anemia that results from erythroid precursors failing to reach maturity in the bone marrow, whereas the numbers of mature myeloid and megakaryocytic cells remain normal. PRCA can be induced by autoimmune processes, infections, drugs, toxins, and radiation, and is diagnosed by a bone marrow cytology examination after excluding the most common causes of nonregenerative anemia. Immunosuppressive therapies are used to treat PRCA, and usuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…After immunosuppressive treatment with cyclosporine and steroid, and hematopoietic stimulation therapy with danazol and rHuEPO, the patient had better control over his AS pain and PRCA. The use of rHuEPO in PRCA is still inconclusive, but De Marchi PN et al [3] believe that rHuEPO can be administered in cases where the immunosuppressants do not provide the desired effect. The literature reports that although the serum EPO level of patients with chronic disease anemia increases with the severity of anemia, it is still relatively insufficient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After immunosuppressive treatment with cyclosporine and steroid, and hematopoietic stimulation therapy with danazol and rHuEPO, the patient had better control over his AS pain and PRCA. The use of rHuEPO in PRCA is still inconclusive, but De Marchi PN et al [3] believe that rHuEPO can be administered in cases where the immunosuppressants do not provide the desired effect. The literature reports that although the serum EPO level of patients with chronic disease anemia increases with the severity of anemia, it is still relatively insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Acquired PRCA may be primary or secondary to some autoimmune/collagen vascular disorders, inflammatory bowel disease, infections, leukemia, thymoma, drugs, or toxins. [13] Ankylosing spondylitis (AS) is one autoimmune disorder with an insidiously progressive and debilitating form of arthritis involving the axial skeleton. However, there is no data about whether AS can complicate with PRCA.…”
Section: Introductionmentioning
confidence: 99%
“…Souza et al [ 125 ] described that after administration of nandrolone decanolate, there was no increase in femoral weight or length and there was no difference in relation to the diameter of the epiphysis and the diaphysis. Marchi et al [ 126 ] found that nandrolone stimulated bone marrow production and it could be used in the treatment of aplastic anemia. In sheep, the beneficial effect of stanozol on articular cartilage regeneration in femorotibial osteoarthritis has been confirmed [ 127 ].…”
Section: Effect Of Anabolic Steroids On Tissuesmentioning
confidence: 99%
“…In that study, the management of dogs with bone marrow suppression included supportive care such as transfusion of blood products, androgenic steroids and broad‐spectrum antibiotics 12 . There have also been a small number of case reports of dogs with bone marrow suppression that responded to treatment with bone marrow stimulants such as lithium chloride and androgens such as nandrolone 13–18 . Romiplostim, a thrombopoietin receptor agonist, has also been successfully used in the treatment of bone marrow suppression secondary to a Sertoli cell tumour 19 .…”
Section: Introductionmentioning
confidence: 99%
“…12 There have also been a small number of case reports of dogs with bone marrow suppression that responded to treatment with bone marrow stimulants such as lithium chloride and androgens such as nandrolone. [13][14][15][16][17][18] Romiplostim, a thrombopoietin receptor agonist, has also been successfully used in the treatment of bone marrow suppression secondary to a Sertoli cell tumour. 19 Despite treatment some dogs never regained full bone marrow function.…”
mentioning
confidence: 99%